(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
This article is about the fact that a person can’t achieve any results with empty words, for this he should set a goal for his future and move forward, every job, every task, everything depends only on goals, aspirations and actions.